Korelasi Kadar Serum Iron Dengan Hemoglobin Pada Pasien Gagal Ginjal Kronik Level V Di RSUD Dr. Harjono S Ponorogo - Yulia Hermawati; Dwi Krihariyani; Syamsul Arifin; Wisnu Istanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Chronic Kidney Disease (CKD) is not merely a condition of permanently decreased renal function, but it also significantly impacts patients’ quality of life. One of the major complications is anemia. Iron deficiency is a primary contributor to anemia in CKD patients, often resulting from reduced erythropoietin production, blood loss during hemodialysis, and inadequate iron intake. This study aims to determine the relationship between serum iron levels (iron in the blood) and hemoglobin levels in stage V chronic kidney disease (CKD) patients undergoing regular hemodialysis at Dr. Harjono S. Ponorogo Regional Hospital, using a quantitative descriptive-analytic approach based on secondary data from the hospital's Laboratory Information System (LIS). A total of 24 CKD patients undergoing hemodialysis twice a week during the period of July to December 2024 were included as research subjects. The results showed that all patients experienced anemia. Although most patients had serum iron levels within the normal range, hemoglobin levels remained low. Statistical analysis revealed a moderate correlation between serum iron and hemoglobin levels, with a statistically significant p-value (p < 0.05) in both examinations. A moderate and statistically significant correlation was found between serum iron and hemoglobin levels in stage V CKD patients, indicating that monitoring iron status is important in the management of anemia in chronic kidney disease.